The Role of Government Public Relations in Stakeholder Collaboration for Sustainable Tourism (Study Case of Ciletuh-Palabuhanratu Geopark) - Choerunnisa, Siti; Nurlaela Arief, Neneng (Journal Research of Social Science, Economics, and Management, 2026)
Ciletuh-Palabuhanratu-Geopark (CPUGGP) is a prestigious site as a UNESCO Global Geopark that is challenged by governance practices to convert formal recognition into sustainable stakeholder management. This research seeks to uncover the policy reasons for participation stagnation and the distinctive essence of the governance model. Adopting a qualitative approach with a case study method, this study conducts in-depth interviews with the Pentahelix actors and processes the data through the fusion of the IAP2 Spectrum of Public Participation and the Four Models of Public Relations. The results display an obvious structural imbalance: The government is in the central "Empower" position, while other parties are relegated to the periphery. This disparity maintains a charade of involvement in which participation means being administratively compliant and visibly ceremonious, rather than being equally co-creative. As a result, the ecosystem falls into the term "Participation Regression," whereby initial enthusiasm dissipates as there is no ongoing dialogic engagement. To address these structural gaps, this research suggests a transformative governance model rooted in Pentahelix Orchestration. The framework recommends a paradigm shift for communication from the technical exchange of information to strategic engagement that builds relationships. The objective is to turn stakeholder participation from episodic, one-off involvement in a procedure into relational engagement and empowered partnership, where passive awareness becomes active, sustainable co-creation.